Organisational barriers to the facilitation of overseas volunteering and training placements in the NHS - John Chatwin; Louise Ackers (BMC Health Services Research, 2018)
Abstract Background Undertaking a period of voluntary work or a professional placement overseas has long been a feature of medical training in the UK. There are now a number of high profile National Health Service (NHS) initiatives aimed at increasing access to such opportunities for staff at all levels. We present findings from a qualitative study involving a range of NHS staff and other stakeholders which explored barriers to participation in these activities. Methods A grounded theory methodology was drawn upon to conduct thematic based analysis. Our data included in-depth, semi-structured interviews with a range of returned volunteers, non-volunteers and other stakeholders (n = 51) who were, or had been, employed by the NHS. Results There are significant barriers to placement and volunteering activity stemming from structural and organisational shortcomings within the NHS. Difficulties in filling clinical roles has a significant impact on the ability of staff to plan and undertake independent placements. There is currently no clearly defined pathway within the NHS by which the majority of grades can apply for, or organise, a period of overseas voluntary or professional placement activity. There were divergent views on the relevance and usefulness of overseas professional placements. Conclusions We argue that in the context of current UK policy initiatives aimed at facilitating overseas volunteer and professional placement activity, urgent attention needs to be given to the structural and organisational framework within which such initiatives will be required to work.